Effect of oxidation level on the inclusion capacity and solution stability of oxidized amylose in aqueous solution. (15th March 2016) - Zhou, Ying; Li, Xinying; Lv, Yongbo; Shi, Yifeng; Zeng, Yu; Li, Defu; Mu, Changdao
Highlights: Amylose was oxidized by hydrogen peroxide through a two-step method. The oxidized amyloses had high oxidation level and carboxyl content. The solubility and solution stability of oxidized amylose-iodine complex were improved. Oxidized amylose could be used to solubilize and stabilize hydrophobic molecules. The two-step method was an efficient way to broaden the applications of amylose. Abstract: The oxidized amyloses with high oxidation level and carboxyl content were successfully prepared through a two-step oxidation method using hydrogen peroxide as the oxidant and copper sulfate as the catalyst. The results showed that oxidation would prevent the oxidized product to crystallize and induce depolymerization of amylose molecules. Accordingly, the helices and inclusion capacity of oxidized amylose molecules were reduced. However, the solubility of oxidized amyloses in water was highly improved due to the introduced carboxyl groups. The solution stability of oxidized amylose-guest inclusion complexes in aqueous solution was efficiently improved to a large extent. The result suggested that the two-step oxidation method was an efficient way to highly broaden the applications of amylose-guest inclusion complexes in water environment.